Peta status kerentanan Aedes aegypti (Linn.) terhadap insektisida cypermethrin dan malathion di Jawa Tengah - Bina Ikawati; Sunaryo Sunaryo; Dyah Widiastuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2015)
The increasing prevalence of Dengue Haemmorhaegic Fever (DHF) is spread through all districts in Indonesia. Dengue Haemorrhagic Fever Control such as vector control, focussing to break DHF transmission. Some research about Ae. aegypti resistance had been done in DHF endemic area in Central Java. Resistance status of Ae. aegypti against insecticide programme promoted by health government in middle and low endemic DHF in Central Java was investigated in this research. Sample collected from 100 houses selected purposively in every village, at every District there were 3 villages selected. Samples consisted of egg, larvae and adult mosquitoes of Ae. aegypti, and reared to get F1. Resistance test of Ae. aegypti done by using WHO susceptibility impregnated paper test procedure. This research showed that Ae. aegypti in all research location had been resistance to malathion 0.8% with mosquitoes mortality average between 13.80%-61.67% and almost all sample is resistance to cypermethrin 0.05% with mosquitoes mortality between 10.00%-63.33% except with sample from Banjarnegara District which has mosquitoes mortality of 84.20%. The conclusion of this research is that Ae. aegypti in all research location had been resistance to malathion. Almost all location resistant to cypermethrin except Banjarnegara District sample which has tolerance level.